2007
DOI: 10.1002/art.22968
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor α suppression of articular chondrocyte phenotype and Sox9 expression in a rat model of osteoarthritis

Abstract: Objective. To define the roles of transforming growth factor ␣ (TGF␣) in cartilage degradation.Methods. Primary rat articular chondrocytes and articular osteochondral explants were cultured with TGF␣ to assess the effects of TGF␣ on chondrocyte physiology and phenotype.Results. TGF␣ altered chondrocyte morphology through reorganization of the actin cytoskeleton and formation of stress fibers. Expression of anabolic genes, including aggrecan, type II collagen, and cartilage link protein, was reduced in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 50 publications
7
81
1
3
Order By: Relevance
“…We have previously shown that TGFa stimulates stress fiber formation in chondrocytes, 8 a phenotype consistent with activation of the RhoA pathway. 15 Therefore, we assessed RhoA activity in primary chondrocyte cultures to determine the ability of TGFa signaling (through EGFR) to activate the RhoA/ROCK pathway.…”
Section: Activation Of Rhoa/rock Signaling By Tgfamentioning
confidence: 72%
See 3 more Smart Citations
“…We have previously shown that TGFa stimulates stress fiber formation in chondrocytes, 8 a phenotype consistent with activation of the RhoA pathway. 15 Therefore, we assessed RhoA activity in primary chondrocyte cultures to determine the ability of TGFa signaling (through EGFR) to activate the RhoA/ROCK pathway.…”
Section: Activation Of Rhoa/rock Signaling By Tgfamentioning
confidence: 72%
“…8 A microplate reader (Tecan US, Durham, NC, USA) was used to quantify the colorimetric reaction by 600 nm absorbance readings.…”
Section: Measurement Of Chondrocyte Cell Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…The most well-established role for Mig-6 in cancer cells is as a negative feedback regulator of EGFR (3)(4)(5)(6), and EGFR signaling is known to play an important role in bone development (28)(29)(30)(31). TGF-α, one of the ligands for EGFR, has been reported to be increased in human osteoarthritic joints (32), and it can induce articular cartilage degradation in animal models (33,34). EGFR signaling appears to be activated in the chondrocytes of the articular cartilage and in the osteophyte of the Mig-6 flox/flox ;Col2a1 Cre knee joints (Fig.…”
Section: Discussionmentioning
confidence: 99%